Modifikasi Algoritma Floyd-Warshall Dalam Menemukan Rute Terpendek Pemadam Kebakaran Di Banyuwangi - Salsabila, Wardatun Naura; Jauhari, Mohammad Nafie (Jurnal Riset Mahasiswa Matematika, 2024)
The research discusses finding fire truck routes on a graph that requires the shortest travel distance from the starting location to the final fire incident location. The objective of this research is to disiminate the application of a modified Floyd-Warshall Algorithm on a graph to find the shortest route for fire trucks. The method used in this study is the Floyd-Warshall Algorithm, which takes the minimum distance from one point to another on the graph and applies a dynamic algorithm, allowing it to correctly select the shortest route. The research results show that testing with the Floyd-Warshall Algorithm produced travel distances with an average effectiveness rate of 3.45%. This percentage indicates that the Floyd-Warshall Algorithm is effective, as it shows a shorter distance. Based on the research findings, it can be concluded that the modified Floyd-Warshall Algorithm applied to the graph can effectively find the shortest route based on the distance between fire stations and incident locations in Banyuwangi, as well as provides information on which routes can be taken based on shorter paths.